2022
DOI: 10.1007/s11831-021-09658-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Modeling and Simulation of Variable-Length Pendulum Systems: A Review

Abstract: A comprehensive review of variable-length pendulums is presented. An attempt at a unique evaluation of current trends in this field is carried out in accordance with mathematical modeling, dynamical analysis, and original computer simulations. Perspectives of future trends are also noted on the basis of various concepts and possible theoretical and engineering applications. Some important physical concepts are verified using dedicated numerical procedures and assessed based on dynamical analysis. At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Examples include its integration into robotics, electromechanical setups such as induction motors, purely electrical networks like dc-dc power converters, and lifting devices like mine elevators or cranes. Moreover, its relevance extends to unconventional domains, contributing to seismic activity detection through inverted pendulum concepts and even playing a role in the development of wave energy converters (WEC), as elaborated by Yakubu, Yurchenko, and others [24,25,26]. This versatility underscores the variable-length pendulum's significance in both theoretical and practical contexts within the realm of dynamic systems and mechatronics.…”
Section: Practical Application Of the Electromagnetic Actuator In The...mentioning
confidence: 95%
“…Examples include its integration into robotics, electromechanical setups such as induction motors, purely electrical networks like dc-dc power converters, and lifting devices like mine elevators or cranes. Moreover, its relevance extends to unconventional domains, contributing to seismic activity detection through inverted pendulum concepts and even playing a role in the development of wave energy converters (WEC), as elaborated by Yakubu, Yurchenko, and others [24,25,26]. This versatility underscores the variable-length pendulum's significance in both theoretical and practical contexts within the realm of dynamic systems and mechatronics.…”
Section: Practical Application Of the Electromagnetic Actuator In The...mentioning
confidence: 95%
“…Currently, there is great activity studying variable-length pendulum systems, such as the swinging Atwood machine [27] and its generalizatins [28], the variable-length coupled pendulums recently studied in [24], or the double variable-length pendulum with counterweight mass [71][72][73]. Variable-length pendulum systems are excellent examples for studying nonlinear dynamics, chaos, and bifurcations.…”
Section: Theorem 11 (Morales-ramis (1999)) If a Hamiltonian System Is...mentioning
confidence: 99%
“…According to a review article [2], the variable-length pendulum system is recognized as highly demanding due to its complex modeling and analysis requirements. However, the authors suggested that a solid understanding of constant-length pendulums can serve as a foundation for creating a more accurate mathematical description of physical processes.…”
Section: Elastic Cord Pendulummentioning
confidence: 99%
“…Variable-length pendulums refer to those whose length can be adjusted either manually or automatically [1]. These pendulums find applications across diverse fields, serving as energy harvesters (e.g., in wave energy converters), load-lifting mechanisms (used in cranes), components in robotics, timekeeping devices, experimental tools, and even attractions in amusement parks [2]. Due to their dynamic or manual length adjustment capability, variable-length pendulums have proven versatile in scientific research, education, and practical contexts [3].…”
Section: Introductionmentioning
confidence: 99%